2022
DOI: 10.3390/app12157526
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Spatial Patterns of Listeria monocytogenes and Salmonella enterica Concentrations in Surface Waters: Empirical Orthogonal Function Analysis of Data from Maryland

Abstract: High spatiotemporal variability of pathogen concentrations in surface waters complicates the design and interpretation of microbial water quality monitoring. Empirical orthogonal function (EOF) analysis can provide spatial patterns (EOFs) of variability in deviations of concentrations in specific locations from the average concentration across the study area. These patterns can be interpreted to assess the effect of environmental factors on pathogen levels in the water. The first and the second EOFs for Lister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…For example, non-tidal rivers and streams are unidirectional and strongly influenced by upstream environmental conditions, but the impact of upstream conditions is reduced for other water types, such as the Great Lakes or seeps fed by groundwater. Past studies that sampled multiple water types often reported drastically different foodborne pathogen prevalence for the sampled water types ( 7 , 12 , 40 , 166 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, non-tidal rivers and streams are unidirectional and strongly influenced by upstream environmental conditions, but the impact of upstream conditions is reduced for other water types, such as the Great Lakes or seeps fed by groundwater. Past studies that sampled multiple water types often reported drastically different foodborne pathogen prevalence for the sampled water types ( 7 , 12 , 40 , 166 ).…”
Section: Discussionmentioning
confidence: 99%